Let $A=\{a_1, a_2, . . .\}$ be a countable subset of R and let λ be the Lebesgue measure on $(\mathbb R,\mathcal M)$. Define for each $k ∈ \mathbb N$

$$U_k =\bigcup_{n=1}^{\infty}(a_n−\frac{1}{2^{n+k}},a_n+\frac{1}{2^{n+k}})$$

Let $N =\bigcap_{m=1}^{\infty}(U_m)$

Show that $λ(N) = 0$.

I'm not sure how to start really:

I assume $$λ(\bigcup_{k=1}^{m}(U_k)) = λ(U_m) \leq \sum_{k=1}^{m}\sum_{n=1}^{\infty}(a_n−\frac{1}{2^{n+k}},a_n+\frac{1}{2^{n+k}})$$

by subadditivity. How do I show that $λ(N)=\bigcap_{m=1}^{\infty}(U_m) = 0$?

Please explain step by step as I am not experienced with this

  • $\begingroup$ You seem to think that $\bigcup_{k=1}^m U_k=U_m$. But $U_1\supseteq U_2\supseteq U_3\supseteq \cdots$, so that's backwards. You can indeed estimate $\lambda(U_k)$ using subadditivity, but only a single sum is called for. The descending nature of the sequence $\{U_k\}$ should be helpful in computing $\lambda(N)$. $\endgroup$ – Harald Hanche-Olsen Oct 25 '16 at 15:11

For every $k\in\{1,2,\dots\}$ we have:$$0\leq \lambda\left(N\right)\leq\lambda\left(U_{k}\right)\leq\sum_{n=1}^{\infty}\lambda\left(\left(a_{n}-\frac{1}{2^{n+k}},a_{n}+\frac{1}{2^{n+k}}\right)\right)=\sum_{n=1}^{\infty}\frac{2}{2^{n+k}}=2^{1-k}$$

This can only be true if: $$\lambda\left(N\right)=0$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.